The Reinvented accounting firm office: Impression management for efficiency, client relations and cost control - Parker, Lee D.; Schmitz, Jana (Accounting, Organizations and Society, 2022)
The office has become a large scale organisational phenomenon accommodating large numbers of organisational employees most often housed in open plan and Activity Based Working settings that arguably resemble the new factory. This study examines contemporary Big 4 accounting firm office design innovations and their representation with a view to eliciting their claimed rationales, reflections of historical office design and management thinking, and apparent strategic agendas with respect to office efficiency, client relations and cost control involved in their offering of professional services. In doing so, it also explores the implications that public practice firms' office design may have for auditor independence and audit quality. Informed by Goffman's theories of impression management, the study employs historical and website analysis, finding a predominant firm focus on office efficiency and client relations with an undercurrent of cost reduction and revenue enhancement aspirations. While represented as innovative current office design and work pattern developments, public practice accounting firm office innovations and intentions are found to significantly reflect historical office design and management thinking, with dramaturgical circumspection of floor designs and props oriented towards creating front stage performances predesigned for clients' impression management. Where backstage redesign and frame breaking does not produce desired employee performance changes, some signs of retreating to more traditional floor redesign and territorial marker usage are evident. The study also signals the potential for innovative accounting firm office designs to carry some significant impacts upon audit independence and audit quality.